Content analysis of oral health information in science textbooks: A cross sectional study in schools of Pune, India - Deepika S Dagar; Pradnya V Kakodkar; Sahana Hegde Shetiya (Wolters Kluwer Medknow Publications, 2020)
Background: Since school textbooks form the base for acquiring knowledge, it is thus important that the information provided in it should be valid. Content analysis helps us evaluate the presence, extent, and validity of the information. Aim: To conduct content analysis of the oral health information in science textbooks of Standard I-X among the schools in Pune. Materials and Methods: A cross-sectional study was conducted among 25 schools, selected using quota sampling (Central Board of Secondary Education [CBSE] [n = 17]:Indian Certificate of Secondary Examination [ICSE] [n = 5]:International Board [n = 1]:Cambridge Assessment International Education [n = 1]:State Board [n = 1]). Convenience sampling was used to recruit the required number of schools. Content analysis was done using an assessment tool of oral health-related core components for different standards based on content, extent, and evidence The data were analyzed descriptively using Microsoft Excel 2013. Results: The study was completed in 21 (84%) schools affiliated to three boards only. A total of 242 pages were analyzed (565 oral health messages and 51 pictures). Of the little information that was present, it was found that the messages and pictures in the books of the CBSE (346 and 29), were more than that in the books of ICSE (166 and 6) and State Board (53 and 6), respectively. The results revealed that the textbooks of all the three boards were lacking in the oral health content with regard to the core components and coverage extent. Conclusions: Science textbooks are lacking in the oral health information, and there is an urgent need to improvise the textbook content.